The Leadership Void for Climate Adaptation Planning: Case Study of the Port of Providence (Rhode Island, United States) - Becker, Austin; Kretsch, Eric (Frontiers in Earth Science, 2019)
Climate adaptation requires leadership from a diverse group of stakeholders to shift investment priorities and generate political will for long-term planning. This is especially true for seaport stakeholders. Ports serve as access points to goods and services from around the world, promoting a higher and more robust quality of life. However, with the increased likelihood of intense storms, rising sea levels, and resource scarcity facing coastal communities, stakeholders will need to adapt coastal infrastructure to ensure long-term viability. Solving such problems requires leadership and participation from government across jurisdictional boundaries and/or the private sector. Using the case of Port of Providence (Rhode Island, United States), this study finds stakeholder perceptions of leadership responsibility contribute to an institutional void, in which it is unclear who is responsible and who should pay for resilience investment.